Development Of Natural-Pozzolan Based Alkali Activated Concrete Incorporating Nano-Silica - Ibrahim, Mohammed (2020)
The primary aim of this research was to develop a natural pozzolan (NP)-based alkali activated concrete (AAC). NP was acquired from the Red Sea coast of Saudi Arabia. The influence of mix design variables on the properties of NP-based AAC were not been investigated earlier including durability of such a concrete when exposed to aggressive environmental conditions. In order to enable its curing at room temperature conditions and attain desirable properties, nanosilica (nSiO2) was incorporated. The morphology, mineralogy and polymerization mechanism of the developed binder were studied in detail. The fresh and hardened characteristics of nSiO2 modified AAC were investigated including its pore structure. The durability of the AAC when exposed to chloride laden environment, acid and sulfates was also evaluated. The results reveal that the superior properties of NP-based alkali activated binder (AAB) were obtained when 400 kg/m3 of precursor material was activated with a combination of sodium silicate (SS) and sodium hydroxide (SH) at a SS/SH ratio of 2.5 having 14M SH solution cured for 7 days at 60 °C. The addition of nSiO2 in the mixture enhanced the strength, morphology and mineralogy of the NP-based AAB when cured at 60 °C as well as room temperature conditions. The nature of the binder was composed of C-A-S-H with Na in the structure with greater absorption of Ca and Al in the case of mixes containing 5% and 7.5% nSiO2. The total pore volume of nSiO2 modified concrete after 28 days of room temperature curing was in the range of 18.35% to 11.23%, the highest in the control mix and the lowest in xxviii the AAC mixture prepared with 5% and 7.5% nSiO2 due to enhanced polycondensation of hydration products. As a result of the improved morphology and mineralogy of the AAB modified with nSiO2, durability was remarkably enhanced. The chloride migration coefficient was 12.82, 12.63, 10.52, 7.83 and 6.22 m2/s (x10-12) and the gravimetric weight loss of the reinforcement embedded in the concrete was 1.608, 0.992, 0.793, 0.670 and 0.681% in the AAC modified with 0, 1, 2.5, 5 and 7.5% nSiO2, respectively. The resistance of AAC prepared with 5% and 7.5% nSiO2 exposed to 5% H2SO4 and sulfate solutions was significantly improved than the other replacement levels. Based on the outcomes, it can be concluded that the NP can be utilized to produce structurally viable AAC for practical applications. The inclusion of nSiO2 in the mixture enabled it to be cured at room temperature conditions. Moreover, the performance of the AAC was either comparable to or better than the OPC-based concrete in all aspects studied in this research. Therefore, the use of the developed AAC particularly that cured at room temperature will lead to the benefits including environmental, economic and technical.